Implementation Challenges of the Public Finance - Ngwenya, Siphiwe Sipho Aubrey (My University, 2011)
This research investigated the challenges on the implementation of the Public Finance Management Act (PFMA) No. 1 of 1999 on improving Liquor regulation in Gauteng. The study confines itself with the challenges of implementing the PFMA on improving the effective liquor regulation in Gauteng. The research involved extensive literature review on the public finance management as well as the Public Sector Reform. This research is an exploratory study on how the PFMA can be an important tool to effective service delivery in the public service in South Africa. Primary data was gathered through in-depth interviews with key stakeholders and document analysis. The key findings of this research suggest that non-compliance to the PFMA has an impact to service delivery due to improper usage of public finances which are aimed at meeting the needs of communities. In conclusion, the findings of the study identify a need for structural changes and introduction of compliance systems to monitor the implementation of the PFMA and other respective regulations/legislation, with the aim of bringing significant improvement on the functioning of the Gauteng Liquor Licensing Office
MM - P&DM
Keywords: Public Finance Management Act; Gauteng liquor regulation; Liquor licences